2004
DOI: 10.3354/meps283233
|View full text |Cite
|
Sign up to set email alerts
|

Linking fish and prawns to their environment: a hierarchical landscape approach

Abstract: Little is known about the relative influence of landscape structure on the spatial distribution and abundance of marine organisms. To address this problem, we applied landscape ecology concepts and methods, together with conventional sampling techniques and path analysis, to test alternative hypotheses of linkages between marine nekton and landscape structure in Moreton Bay, Queensland (Australia). We quantified substratum structure at 3 spatial scales: (1) whole landscape mosaic (10s of hectares); (2) habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 115 publications
4
132
0
1
Order By: Relevance
“…A pattern of peaks and troughs persisted regardless of the temporal and spatial variation in the data set (Stead et al 2005). The three-dimensional structure of habitat provides a strong predictor of the body masses of the species dependent upon that habitat (Gutierrez and Iribarne 2004), and others continue to document a relationship between discontinuities in body size distributions and habitat structure in freshwater fish (Fu et al 2004) and nekton (Pittman et al 2004). Robson et al (2005) argued that studies must once again emphasize habitat structure and body mass to refine the methodology and synthesize results from pattern seeking and mechanistic research.…”
Section: Cross-scale Patterns: Ecosystemsmentioning
confidence: 99%
“…A pattern of peaks and troughs persisted regardless of the temporal and spatial variation in the data set (Stead et al 2005). The three-dimensional structure of habitat provides a strong predictor of the body masses of the species dependent upon that habitat (Gutierrez and Iribarne 2004), and others continue to document a relationship between discontinuities in body size distributions and habitat structure in freshwater fish (Fu et al 2004) and nekton (Pittman et al 2004). Robson et al (2005) argued that studies must once again emphasize habitat structure and body mass to refine the methodology and synthesize results from pattern seeking and mechanistic research.…”
Section: Cross-scale Patterns: Ecosystemsmentioning
confidence: 99%
“…Previous authors have noted that there is no single correct scale at which to quantify the spatial distribution of populations and have suggested that habitat use must be examined on multiple scales (Wiens 1989, Levin 1992. Recently, the importance of scale in the interpretation of spatial distribution of aquatic organisms has been noted (Essington & Kitchell 1999, Maury et al 2001, Pittman et al 2004). Essington & Kitchell (1999) showed telemetered largemouth bass distributions in a small Michigan lake were the product of several processes operating at spatial scales of 10, 30, and 180 m. The authors concluded that the small-scale aggregation may have been a response to patches of aquatic macrophytes, while large-scale variation was a response to selection of the eastern half of the lake, possibly due to warmer water temperatures.…”
Section: Importance Of Scalementioning
confidence: 99%
“…Habitat richness was also of low importance, regardless of model type and spatial scale. Although this corresponds to findings from other studies (e.g., [16,17]), the question remains whether other measures of the spatial composition of habitats, e.g., taking into account functional differences or complementarities between habitat types [63], would contribute more to predictions of the fish community variables. The success of landscape composition metrics in terrestrial spatial ecology [64] suggests that this is an important avenue for future research.…”
Section: Discussionmentioning
confidence: 71%
“…In the random forest models, the high importance of geomorphic zone for predictions of all response variables is interesting because this predictor has been investigated by very few studies [13], including several that have explored the use of a large variety of metrics for quantifying the seascape (e.g., [16][17][18]32,61]). The importance of geomorphic zone in our study may be a function of the spatial extent of our study area, a function of the high accuracy with which this variable was mapped, a function of its collinearity with another predictor, and/or a true description of the importance of reef geomorphology for structuring the spatial distribution of the three response variables in our study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation